Building 21st century entrepreneurship - D'Andria, Aude; d uthor (London, UK : ISTE, Ltd. ; Hoboken, NJ : Wiley, 2017)
An original essay supported on recognized academic readings. It is also illustrated with several case studies and socio-economic information on a global scope. It presents a substantial body of knowledge about entrepreneurship in a theoretical and pragmatic way in order to help readers to understand what means entrepreneurship today. Principal questions studied in this book are: who are the new figures of entrepreneurs and how are they creating the companies of the future?
Entrepreneurship and High Heels -- Entrepreneurship for All Ages -- Entrepreneurship Without Limits -- The Entrepreneurial Connection -- Improving the Expansion of Business Creation -- Building New Theories to Understand Entrepreneurship -- Conclusion: What's Next? New Business Models for a New Economy.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed June 1, 2017).
John Wiley and Sons
Keywords: Entrepreneurship; Entrepreneuriat; entrepreneurs; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Entrepreneurship